Řízení rizik ve stavebním podniku - Kovalčíková, Barbora (Vysoké učení technické v Brně. Fakulta stavební, 2021)
Bakalářská práce se zaměřuje na Řízení rizik ve stavebním podniku. Práce je rozdělena na dvě části. Teoretická část podává informace o riziku v projektech, základním rozdělení a řízení. Praktická část pracuje se získanými teoretickými znalostmi na konkrétní stavební zakázce, zahrnuje identifikaci rizik, ohodnocení rizik a návrh preventivních opatření za účelem snížení dopadu rizik nebo jejich úplnou eliminaci.

The bachelor’s thesis is focused on Risk management in a construction company. The thesis is divided into the theoretical and practical part. The theoretical part is dedicated to information about risk in projects, basic division and control. The practical part pays closer attention to a specific construction contract, in which case the acquired theoretical knowledge is applied. Furthermore, it includes the identification of risks, their evaluation and the motion of the precautions against increasing their impact or elimination.
Risk Management inside Construction Company
Keywords: Riziko; identifikace rizik; nebezpečí; pravděpodobnost; management rizika; monitorování a kontrola rizik; analýza rizika; SWOT analýza; RIPRAN; hodnota rizika; opatření rizika; ošetření rizik; vyhodnocení.; Risk; risk identification; hazard; probability; risk management; risk monitoring and control; risk analysis; SWOT analysis; RIPRAN; value risk; risk treatment; evaluation.